Online sales funnel as an analytical tool for business efficiency management - E. Vasilieva; V. Loseva (Управление)
The possibilities of online sales strategy analysis based on unit-economy metrics (Unit Economics is a new economic modeling method used to determine the effectiveness of a digital business model by assessing the profitability of a product unit or a single customer), as well as on the theory of restrictions, have been shown. The peculiarities of settings of problems on monitoring the process of attracting customers to the electronic resource of a company, and their support up to conclusion of commercial transaction (product sale) have been revealed. A scenarios matrix for promoting information about a product, a brand, or a service using various communication channels has been compiled.Among various strategies of a sales funnel management the following three main strategies have been highlighted: the strategy of a proportional expansion (when increasing a traffic at the entrance of a funnel, which gives a large conversion, the funnel expands at all next stages, and the output result is increased); the strategy of stretching (increasing of a conversion at each level results in the output increasing), and the strategy of a key level (this strategy demands to determine the level of the funnel, which limits the entire system, and to apply efforts to improve conversion indicators at this special level). A methodology for constructing and analyzing the product funnel using unit-economy metrics has been adduced. The peculiarities of development of strategies for sales funnel using the critical-chain method (Critical Chain Management, CPM) and method of Theory of Constraints (TOC) have been highlighted, when the company’s results depend on the interacting elements of the system, that create the constraints. A method of searching bottlenecks in the sales funnel has been proposed, which consists in a consistent assessment of the impact on the profits of each of its five basic metrics, for each of which there are special development tools, allowing one to find points of rapid profit growth. Scenario analysis of sales funnel using unit metrics has been сarried out.